An aptamer that neutralizes R5 strains of HIV-1 binds to core residues of gp120 in the CCR5 binding site - Cohen, C; James, W; Forzan, M; Sproat, B; Pantophlet, R; McGowan, I; Burton, D (Elsevier, 2008)
We have previously isolated nucleic acid ligands (aptamers) that bind the surface envelope glycoprotein, gp120, of HIV-1, and neutralize infection of diverse sub-types of virus. Our earlier studies have identified the overall structure of one of these aptamers, B40, and have indicated that it binds to gp120 in a manner that competes with that of the HIV-1 coreceptor, CCR5, and select “CD4i” antibodies with epitopes overlapping this region. Here, we sought to map the B40 binding site on gp120 more precisely by analysing its interaction with a panel of alanine substitution mutants of gp120. Furthermore, we tested our hypothesis concerning the structure of the 40 nucleotide functional core of the aptamer by the solid-phase synthesis of truncated and chemically modified derivatives. The results confirm our structural predictions and demonstrate that aptamer B40 neutralizes a diverse range of HIV-1 isolates as a result of binding to relatively conserved residues on gp120 at the heart of the CCR5-binding site. These structural insights may provide the basis for the development of potential anti-viral agents with high specificity and robustness.